Development of models of call center with the system of interactive voice response - Федюшин, Олександр Іванович; Баленко, Олексій Іванович (Technology audit and production reserves, 2015)
The analysis of literature indicates no serious research of call center, which would take into account the impact of interactive voice response (IVR), but at the same time, experience shows that its introduction significantly affects the operational costs of the system owner. That is why the development of adequate models of functioning call center is quite urgent task when designing for leading to the improvement of operation and, therefore, reduces the cash costs of their operation. The work was performed statistical analysis, and the data on the work of the Call-center, a queuing system. IVR system performance was investigated on the developed simulation model in the system GPSS World, experimental studies of developed methods and algorithms are conducted. Number of calls that were serviced, the percentage of lost calls of operators, histogram average waiting time in the queue at different values of the number of working operators, histogram queue length are obtained. They allow predicting the workload of the Call-center, and calculating based on the number of operators required. The research results show that changing the length of the IVR only a few seconds significantly affects the quality parameters of call-center such as the percentage of lost or rejected calls, average wait time, average queue length for operators. With increasing served IVR calls that left behind this system, the average call time in the queue and the average queue length to operators significantly reduced, and the simulation model allows tracking statistics module. Developed and statistical simulation models can be used in the design and operation of call-centers. In the future, it is proposed researching models on the more complex models of call distribution than normal, or exponential.